Peer Interaction in the L2 Classroom: A Study among Malaysian ESL Learners - Soh, Siak Bie; Tam, Shu Sim; Nikitina, Larisa (Issues in Language Studies, 2021)
Adopting a cognitive-interactionist perspective, this study focused on peer interaction in the L2 classroom. It explored types of peer interaction in terms of Negotiation of Meaning (NoM), Language-related Episodes (LRE) and Uptake of Recast that tend to prevail during task discussions in the L2 classroom. This study also assessed whether task complexity and task condition influenced L2 peer interaction. Thirty-six (N=36) Malaysian university students learning English as a second language participated in this study. The tasks were designed at two levels of cognitive complexity, namely, simple tasks with two causal reasoning demands and complex tasks with six causal reasoning demands. Each participant was involved in peer discussion sessions of simple and complex tasks in dyadic and triadic groupings. The findings revealed that clarification requests during the NoM were the most prominent feature of the peer interaction. A paired sample t-test showed that statistically significant difference was detected between the dyadic and triadic settings for the comprehension check feature (NoM), the incorrectly resolved episodes (LRE) and the unmodified uptake of recast. The article concludes with a discussion of theoretical and pedagogical implications from these findings.